Ecological Function of Phenolic Compounds from Mediterranean Fucoid Algae and Seagrasses: An Overview on the Genus Cystoseira sensu lato and Posidonia oceanica (L.) Delile - Mannino, Anna Maria; Micheli, Carla (Journal of Marine Science and Engineering, 2020)
Biodiversity is undergoing rapid and worrying changes, partially driven by anthropogenic activities. Human impacts and climate change (e.g., increasing temperature and ocean acidification), which act at different spatial scales, represent the most serious threats to biodiversity and ecosystem structure and function. In the Mediterranean Sea, complex systems such as fucoid algae and seagrasses, characterized by a high associated biodiversity, are regularly exposed to natural and anthropogenic pressures. These systems, particularly sensitive to a variety of stressors, evolved several physiological and biochemical traits as a response to the different pressures which they are subjected to. For instance, they produce a huge quantity of secondary metabolites such as phenolic compounds, to adapt to different environmental stressors and to defend themselves from biological pressures. These natural products are receiving increasing attention due to their possible applications in a wide range of industrial sectors. In this paper we provide an overview on the ecological role of phenolic compounds from the genus Cystoseira sensu lato and Posidonia oceanica (L.) Delile, also highlighting their potential use as ecological biomarkers.